Wood processing by-products treated with the lignin-based conditioner as mulch for soil protection - Shulga, Galia; Betkers, Talrits; Vitolina, Sanita; Neiberte, Brigita; Verovkins, Anrijs; Anne, Olga; Ambrazaitiene, Dalia; Zukauskaite, Audrone (Journal of Environmental Engineering and Landscape Management, 2015)
Wood processing by-products such as bark of different wood species and hydrolysis lignin were applied as soil mulch. The lignin-based soil conditioner (LSC) representing a lignin-based polyelectrolyte complex with the different composition (a lignin/polymer mass ratio) was obtained under laboratory conditions and was intended to protect sandy soil from erosion by simultaneous application of a soil conditioner as an adhesive, mulch and plant seeds by hydroseeding. The study revealed the pronounced dependence of the properties of the treated wood-originated mulch on the wood species as well as on the composition, the applied concentration and the application rate of LSC. A comparison of the obtained results showed that the treated hydrolysis lignin was characterised by higher compressive strength, higher water resistance and lower moisture losses from sandy soil for a given LSC composition and application rate than the bark-based mulch. The conditioner concentrations don’t have negative impact on the germination of seeds plants of the coastal dune zone. First published online: 21 Oct 2015